Impacto de las modalidades de pensión en el régimen de ahorro individual con solidaridad en Colombia (2019)
The Political Constitution of Colombia of 1991 as the legal basis of our Stateincludes a series of right sthatallow people their own realization, Social Security beingone of therightsenshrined in the Charter, guaranteing people and in particular -cialtoworkersthecoverage of thedifferentcon tingenciesthattheymaypresentthroughouttheir labor and economically active stagewiththeaim of providingthemwithstability and decentlifewhentheirabilitytoworkisaffected. In thissense, Colom bian labor legislation has establishedthecriteriathatmust be takenintoaccount in relationtothe So cial Security System, thusLaw 100 of 1993 wasissued, whoseregulatoryframeworkconstitutesone of themostsignificantchanges in thesystem of pensions in the country, creating a dual autono mous and independentpensionsystem: a Medium Premium Regime (RPM) and a secondregime thatwill be thebasis of ourstudy and isknown as the Individual SavingswithSolidarityRegime (RAIS), thewhichismanagedbythepensionfund managers (AFP), thatis, byprivatefunds. Then, withrespecttowhatisstated in theregulationsrelatedtothe Individual SavingswithSolidari tyRegime (RAIS) whentheworkerchoosesthis regimetomakehisvoluntarycontributionstothesys tem, he addressesthepossibility of selectingamongseveraltypes of pensionmodalities, in charge of thepensionfundadministrators (AFP) and others in charge of thepensioner'schoiceinsurer. However, theNationalGovernment, in anattempttoimproveColombians' confidence in thesystem, as well as increasingitscoverage and efficiency, consideredtheneedtoestablish new pensionmo dalities in the Individual SavingswithSolidarityRegime (RAIS), then, as a result of thisneed, Cir cular 013 of 2012 isissuedbytheFinancialSuperintendence. Meanwhile, theresearchfocusesonana lyzing and contextualizingtheimpact of theold-agepensionmodalities in the Individual Saving swithSolidarityRegime in Colombia and, in thisway, identifyingtheelements and characteristics of thedifferentmodalities; recognizetheadvantages, disadvantages and differences of eachone of them, so thattheaffiliatedpopulationmanagestochoosetheonethatsuitstheir particular interests and needs.